Penerapan Metode Hazop dalam Identifikasi Bahaya dan Pengendalian Risiko K3 pada Proyek LRT Jakarta Fase 1B - Indra, Najwa Putri; Arifin, Ari Syaiful Rahman; Rifwan, Fitra; Andayono, Totoh (LPPM Universitas Dharma Andalas, 2026)
LRT (Integrated Rail Transit) is a public transportation system developed by PT. Kereta Api Indonesia (KAI) to facilitate mobility for residents of Greater Jakarta (Jabodetabek). The objectives of this study are: 1) identifying high-risk construction projects, 2) applying the HAZOP method to identify hazards and deviations in work processes, 3) assessing risk levels based on likelihood and severity parameters, and 4) providing risk control recommendations based on the HAZOP analysis results. This research is a descriptive analytical study with a qualitative-quantitative approach, conducted on the Jakarta LRT Phase 1B Project, Velodrome–Manggarai Segment, implemented in January 2026. Data collection involved field observations, interviews, questionnaires, and documentation. The results indicate: 1) Identification of High-Risk Work: High-risk construction work in the LRT Phase 1B project includes the use of heavy equipment (jack hammers), concrete casting, girder lifting, electrical installation, and welding processes. 2) The application of the HAZOP method is effective in identifying potential hazards and deviations in various work processes. 3) Risk assessment based on likelihood and severity indicates the greatest risks are in girder lifting and concrete casting. 4) Risk control through technical measures (e.g., low-vibration work methods, strict supervision, use of PPE), administrative measures (SOPs, training), and physical protection (electrical protection, barricades) is essential to reduce occupational risks.